Pengembangan Panduan Pelatihan Teknik Self Control untuk Mereduksi Perilaku Agresif Fisik Siswa SMA - Maria Gregoria Nona Diogo; Blasius Boli Lasan; IM Hambali (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This study aims to produce a technique training guide self-control to reduce physical aggressive behaviour of high school students by meeting the acceptance criteria product through expert testing of guidance and counselling materials, learning media expert testing and prospective user testing. This research and development research uses the research and development model of Borg & Gall (1983). The subjects of this research are BK experts, media experts and potential users. The feasibility of this guide is based on an assessment carried out by two BK experts, two learning media experts and two potential users. The data obtained in this research and development are in the form of numerical data and verbal data. Analysis of the results of the expert and prospective user assessments used the analysis inter-rater agreement model to determine the level of acceptance of the guide. The results of the assessment from the BK expert gave an assessment of 1.00 which had a very high validity number, the media expert gave an assessment of 1.00 which had a very high validity number and prospective users gave an assessment of 1.00 which had a very high validity number so that it can be concluded that the guide developed to meet product acceptance criteria.Abstrak: Penelitian ini bertujuan untuk menghasilkan panduan pelatihan teknik self-control untuk mereduksi perilaku agresif fisik siswa SMA dengan memenuhi kriteria keberterimaan produk melalui uji ahli materi bimbingan dan konseling, uji ahli media pembelajaran dan uji calon pengguna. Kemudian penelitian dan pengembangan ini menggunakan model penelitian dan pengembangan Borg & Gall (1983). Subjek pada penelitian ini yaitu ahli BK, ahli media dan calon pengguna. Perolehan data pada penelitian dan pengembangan ini menggunakan analisis inter-rater agreement model untuk mengetahui tingkat keberterimaan panduan. Hasil penilaian dar ahli BK memberikan nilai 1,00 yang memiliki angka validitas sangat tinggi, ahli media memberikan nilai 1, 00 yang memiliki angka validitas sangat inggi, dan calon pengguna memberikan nilai 1,00 yang memiliki angka validitas sangat tinggi, sehingga disimpulkan bahwa panduan yang telah dikembangkan memenuhi kriteria keberterimaan produk.